Moi, Conchita - Wurst, Conchita; Bachmann, Daniel Oliver; Gaultier, Jean Paul; Schmidt, Olivier (Paris : Archipel, 2015)
Fonds Suzan Daniel (FSD)
Titel op de voorpagina: Moi Conchita : rien ne nous arrètera : Conchita Wurst : mon histoire
Frans
Monografie